Discrete wavelet transform and back-propagation neural networks algorithm for fault location on single-circuit transmission line - Ngaopitakkul, Atthapol; Pothisarn, Chaichan (My University, 2008)
This paper proposes a technique using discrete wavelet transform (DWT) and back-propagation neural network (BPNN) for locating of fault location on single circuit transmission lines. The ATP/EMTP was used to simulated fault signals. The mother wavelet daubechies4 (db4) is employed to decompose, high frequency component from these signals. The first peak time in first scale of each bus that can detect fault are used as input pattern for the training pattern. It is shown that the proposed technique gives satisfactory. © 2008 IEEE.
Keywords: ATP/EMTP; Backpropagation neural network; Fault Location; Transmission line; Wavelet transform